(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article discusses the importance of individual and collective learning. Using a combination of individual and group learning methods makes the learning process more effective and allows you to use the strengths of both approaches. Learning English individually and as a team a starting idea for research on importance of “The methods of learning English independently and collectively are unique advantages, disadvantages and impact on the educational process.